Marker‐free genetic engineering of the chloroplast in the green microalga Chlamydomonas reinhardtii. Issue 7 (7th May 2013) - Chen, Hsu‐Ching; Melis, Anastasios
Summary: The work applied a transgene expression method based on the replacement of an inactive rbcL gene as the selection marker in Chlamydomonas reinhardtii chloroplasts. The native rbcL gene in strain CC2653 has a point mutation that causes early translation termination, thus resulting in a photosynthesis mutant. Recovery of rbcL function for selection is offered along with the heterologous expression of the alcohol dehydrogenase ADH1 gene from Saccharomyces cerevisiae in the Chlamydomonas chloroplast. The CrCpADH1 gene was inserted via double homologous recombination in the psaB‐rbcL chloroplast intergenic region of recipient strain CC2653, using the psaB and rbcL gene sequences for the double homologous recombination. This transformation conferred a functional rbcL gene and expression of the CrCpADH1 transgene in the recipient strain. This method alleviated the need to use antibiotics for selection, resulting in a negligible number of false positives during screening, and attaining a transformation efficiency greater than 90%. The approach also ensured segregation of chloroplast DNA copies, so as to achieve homoplasmy of the transformant chloroplast DNA, with a concomitant elimination of recipient strain Cp DNA. High levels of steady‐state CrCpADH1 transcripts were detected in the homoplasmic transformants. However, CrCpADH1 protein levels were attenuated under continuous illumination growth conditions due to oxygen accumulation in the cells. Under conditions of low oxygen partial pressure, or anoxia, accumulation of CrCpADH1 protein in the cells and ethanol in the growth medium was observed. A metabolic pathway for ethanol production is proposed in Chlamydomonas, mediated by the chloroplast‐localized CrCpADH1 transgenic enzyme.